68Ga-Prostate-Specific Membrane Antigen Positron Emission Tomography Maximum Standardized Uptake Value as a Predictor of Gleason Pattern 4 and Pathological Upgrading in Intermediate-Risk Prostate Cancer. Issue 2 (21st February 2022) - Xue, Alan L.; Kalapara, Arveen A.; Ballok, Zita E.; Levy, Sidney M.; Sivaratnam, Dinesh; Ryan, Andrew; Ramdave, Shakher; O'Sullivan, Richard; Moon, Daniel; Grummet, Jeremy P.; Frydenberg, Mark
Abstract : Purpose: Accurate risk stratification remains a barrier for the safety of active surveillance in patients with intermediate-risk prostate cancer. [ 68 Ga]Ga-PSMA-11 prostate-specific membrane antigen positron emission tomography/computerized tomography ( 68 Ga-PSMA PET/CT) and the maximum standardized uptake value (SUVmax) may improve risk stratification within this population. Materials and Methods: We reviewed men with International Society for Urological Pathology Grade Group (GG) 2–3 disease on transperineal template biopsy undergoing 68 Ga-PSMA PET/CT from November 2015 to January 2021. Primary outcome was the presence of high percentage Gleason pattern 4 (GP4) disease per segment at surgery at 3 thresholds: >/<50% GP4, >/<20% GP4, and >/<10% GP4. SUVmax was compared by GP4, and multivariable logistic regression examined the relationship between SUVmax and GP4. Secondary outcome was association between SUVmax and pathological upgrading (GG 1/2 to GG ≥3 from biopsy to surgery). Results: Of 220 men who underwent biopsy, 135 men underwent surgery. SUVmax was higher in high GP4 groups: 5.51 (IQR 4.19–8.49) vs 3.31 (2.64–4.41) >/<50% GP4 (p <0.001); 4.77 (3.31–7.00) vs 3.13 (2.64–4.41) >/<20% GP4 (p <0.001); and 4.54 (6.10–3.13) vs 3.03 (2.45–3.70) >/<10% GP4 (p <0.001). SUVmax remained an independent predictor of >50% (OR=1.39 [95%CI 1.18–1.65], p <0.001) and >20% (OR=1.24 [1.04–1.47], p=0.015) GP4 disease per-segment, and of pathological upgrading (OR=1.22 [1.01–1.48], p=0.036). SUVmax threshold 4.5 predicted >20% GP4 with 58% specificity, 85% sensitivity, positive predictive value 75% and negative predictive value 72%. Threshold 5.4 predicted pathological upgrading with 91% specificity and negative predictive value 94%. Conclusions: SUVmax on 68 Ga-PSMA PET/CT is associated with GP4. SUVmax may improve risk stratification for men with intermediate-risk prostate cancer.